Keratins determine network stress responsiveness in reconstituted actin-keratin filament systems - Elbalasy, Iman; Mollenkopf, Paul; Tutmarc, Cary; Herrmann, Harald; Schnauß, Jörg (Soft Matter, 2021)
The cytoskeleton is a major determinant of cell mechanics, and alterations in the central mechanical aspects of cells are observed during many pathological situations. Therefore, it is essential to investigate the interplay between the main filament systems of the cytoskeleton in the form of composite networks. Here, we investigate the role of keratin intermediate filaments (IFs) in network strength by studyingin vitroreconstituted actin and keratin 8/18 composite filament networksviabulk shear rheology. We co-polymerized these structural proteins in varying ratios and recorded how their relative content affects the overall mechanical response of the various composites. For relatively small deformations, we found that all composites exhibited an intermediate linear viscoelastic behaviour compared to that of the pure networks. In stark contrast, when larger deformations were imposed the composites displayed increasing strain stiffening behaviour with increasing keratin content. The extent of strain stiffening is much more pronounced than in corresponding experiments performed with vimentin IF as a composite network partner for actin. Our results provide new insights into the mechanical interplay between actin and keratin filaments in which keratin provides reinforcement to actin. This interplay may contribute to the overall integrity of cells. Hence, the high keratin 8/18 content of mechanically stressed simple epithelial cell layers, as found in the lung and the intestine, provides an explanation for their exceptional stability.
CRIS-Team Scopus Importer:2021-04-23